Communicating knowledge - Bedford, Denise; Chalphin, Ira; Dietz, Karen; Phlypo, Karla (Bingley, U.K. : Emerald Publishing Limited, 2022)
The communication of knowledge is a core concept in the field of knowledge management and an essential new role and responsibility of business managers. Knowledge capital is the primary source of wealth and the key source of productivity in the knowledge economy. Stockpiling and storing knowledge diminishes its value. It is only through circulation that our knowledge capital realizes its business value. Communicating Knowledge addresses essential management practices in the 21st-century knowledge economy. It speaks to the change that every organization is experiencing as they transition from an industrial to a knowledge organization. The COVID-19 pandemic has heightened an awareness of communications practices in the past year, with communication norms and behaviors being challenged at every level. How we communicate, when we communicate, with whom we communicate, and what we communicate is currently undergoing a global reform. Communication competencies are no longer desirable qualities in managers - they are essential. This book is intended for business managers working at all levels, knowledge management practitioners and scholars, communications professionals, practitioners, and consultants.
Section 1. Communicating knowledge -- Chapter 1. Shifting landscape of organizational communications -- Chapter 2. Communicating knowledge in the new world of work -- Chapter 3. Knowledge capital and knowledge mobilization -- Chapter 4. Designing management communication for the knowledge economy section 2. Communicating knowledge assets -- Chapter 5. Communicating human capital -- Chapter 6. Communicating structural capital -- Chapter 7. Communicating relational capital section 3. Key issues in knowledge communications -- Chapter 8. Discernment as a management issue -- Chapter 9. Listening as a management issue -- Chapter 10. Facilitation as a management issue -- Chapter 11. Decision making as a management issue -- Chapter 12. Team building as a management issue section 4. Building communications competencies and capacity -- Chapter 13. Building communications competencies -- Chapter 14. Building communications capacity appendix a. Pulling it all together.
Includes index.
Includes bibliographical references.
Keywords: Knowledge management; Communication in management; Business & Economics -- Information Management; Knowledge management